2006
DOI: 10.1093/ecam/nek005
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Green Propolis Protects against Retinal Damage In Vitro and In Vivo

Abstract: Propolis, a honeybee product, has gained popularity as a food and alternative medicine. Its constituents have been shown to exert pharmacological (anticancer, antimicrobial and anti-inflammatory) effects. We investigated whether Brazilian green propolis exerts neuroprotective effects in the retina in vitro and/or in vivo. In vitro, retinal damage was induced by 24 h hydrogen peroxide (H2O2) exposure, and cell viability was measured by Hoechst 33342 and YO-PRO-1 staining or by a resazurin–reduction assay. Propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 37 publications
1
45
0
2
Order By: Relevance
“…The protective and pharmacological effects of propolis on retinal damage have previously been examined in vitro and in vivo [27,28], but these studies did not include electron microscopic examinations. However, Sande et al identified disorganization of photoreceptor outer segments and significant alterations of cell structure, including expanded intracellular spaces containing dense bodies and membranous debris, 24 h and 8 days after injection of hamsters with LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The protective and pharmacological effects of propolis on retinal damage have previously been examined in vitro and in vivo [27,28], but these studies did not include electron microscopic examinations. However, Sande et al identified disorganization of photoreceptor outer segments and significant alterations of cell structure, including expanded intracellular spaces containing dense bodies and membranous debris, 24 h and 8 days after injection of hamsters with LPS.…”
Section: Discussionmentioning
confidence: 99%
“…A própolis verde, encontrada no Brasil na região de Minas Gerais é rica em terpenóides e derivados prenilados do ácido cumárico [3] . Pioneiramente, Alencar et al [16] e Silva et al [40] estudaram a própolis vermelha produzida na região de mangue do Estado de Alagoas, baseandose principalmente na sua composição química rica em isoflavonóides e alta atividade antimicrobiana e classificaram como um novo tipo de própolis brasileira (13 º tipo).…”
Section: Características Da Própolis E Seu Impacto Na Saúdeunclassified
“…As abelhas usam essa resina para vedar suas colmeias, protegendo-as assim, de insetos e microorganismos invasores [2] . Mais recentemente, a própolis tem sido utilizada no tratamento de várias doenças por parcela da população de países como Japão, Brasil, Estados Unidos e Europa, bem como, tem sido frequente a utilização como ingrediente em produtos cosméticos [3] . Estudos relatam que a própolis tem uma grande variedade de atividades biológicas tais como a antimicrobiana, antiinflamatória, antioxidante e antitumoral [4][5][6] .…”
Section: Introductionunclassified
“…After anesthesis with a Zoletil (1.6 μg/g, Verbac Laboratories 06515, France) and Rompun (0.05 μl/g, Bayer) mixture, retinal damage was induced by an injection (2 μl/eye) of NMDA (2.5 mM dissolved in 0.01 M PBS) to the left eye using 30 gauge of Hamilton syringe (Inokuchi et al 2006). One drop of 0.5 % moxifloxacin ophthalmic solution (Alcon Laboratories Inc., Fort Worth, USA) was applied topically to the treated eye immediately after the intravitreous injection.…”
Section: Nmda-induced Retinal Damagementioning
confidence: 99%